Nitrification of the lowermost stratosphere during the exceptionally cold Arctic winter 2015 - Braun, Marleen; Grooß, Jens-Uwe; Woiwode, Wolfgang; Johansson, Sören; Höpfner, Michael; Friedl-Vallon, Felix; Oelhaf, Hermann; Preusse, Peter; Ungermann, Jörn; Sinnhuber, Björn-Martin; Ziereis, Helmut; Braesicke, Peter (Atmospheric Chemistry and Physics, 2019)
Observation of nitrification of the lowermost stratosphere during the cold Arctic winter 2015 using the Research aircaraft HALO.